2018
DOI: 10.1186/s12935-018-0616-x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hypermethylated in cancer-1 by miR-4532 promotes adriamycin resistance in breast cancer cells

Abstract: BackgroundMicroRNAs are small RNAs (~ 22 nt) that modulate the expression of thousands of genes in tumors and play important roles in the formation of multidrug resistance. In this study, we firstly investigated that miR-4532 involved in the multidrug resistance formation of breast cancer by targeting hypermethylated in cancer 1 (HIC-1), a tumor-suppressor gene.MethodsTo identify and characterize the possible miRNAs in regulating multidrug resistance, we employed the transcriptome sequencing approach to profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Another study has also highlighted the restored expression of miR-29a in AML [30]. Furthermore, consistent with our results, miR-4532 is highly expressed in breast cancer [12]. Generally, miRs interact with their target genes at specific sites and regulate expression of respective target genes of miRs at a post-transcriptional level [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study has also highlighted the restored expression of miR-29a in AML [30]. Furthermore, consistent with our results, miR-4532 is highly expressed in breast cancer [12]. Generally, miRs interact with their target genes at specific sites and regulate expression of respective target genes of miRs at a post-transcriptional level [31].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, aberrant miRs have also been implicated in various hematologic malignancies like AML [11]. A study conducted by Feng et al demonstrated the promoting role of miR-4532 overexpression in drug resistance of breast cancer cells [12]. Moreover, miR-4532 was predicted to possess putative binding site of the leucine zipper downregulated in cancer-1 (LDOC1) gene by online prediction software.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TFEB can activate the phosphorylation of STAT3 and AKT to promote breast cancer metastasis receptor (LIFR) could promote STAT3 activation and contribute to breast cancer resistance to Trastuzumabemtansine (T-DM1) [73]. Furthermore, miR-4532 is found to suppress hypermethylated in cancer-1 (HIC-1) and IL-6/STAT3 to promote Adriamycin resistance in breast cancer [74].…”
Section: The Role Of Stat3 In Breast Cancer Chemoresistancementioning
confidence: 99%
“…Meanwhile, other papers have reported that miR-4532 promotes tumor progression and that miR-6126 suppresses tumor progression. Breast cancer cells overexpressing miR-4532 have enhanced cell viability upon administration of adriamycin ( 37 ). miR-4532 targeting hypermethylation in cancer 1 (HIC-1), and overexpression of HIC-1 in breast cancer cells suppresses cell invasion in Transwell assays ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer cells overexpressing miR-4532 have enhanced cell viability upon administration of adriamycin ( 37 ). miR-4532 targeting hypermethylation in cancer 1 (HIC-1), and overexpression of HIC-1 in breast cancer cells suppresses cell invasion in Transwell assays ( 37 ). Conversely, enhanced expression of miR-6126 suppresses ovarian cancer progression.…”
Section: Discussionmentioning
confidence: 99%